Cost-effectiveness of antiviral therapy in chronic hepatitis C (G1) - A. V. Rudakova; D. A. Gusev; A. N. Uskov; Yu. V. Lobzin (Журнал инфектологии, 2016)
Updated HCV clinical guidelines placed direct acting agents (DAAs) as the preferable the first line regimens.The objective of the study was PE assessment of HCV therapy among G1 naïve patientsMethods: Analysis is based on data of randomized clinical trials and average price of HCV medicines from state auctions placed in state procurement system in 2015.Results: PTV/OBV/DSV/r cost is 30,5% lower vs PegIFN/RBV/SMV. In comparison with PegIFN/RBV/BCV combination PTV/OBV/DSV/r is cost saving by 10,6% at patients without cirrhosis and 36,2% at patients with cirrhosis. DCV/ASV combination is chipper PTV/OBV/DSV/r and it would be used for G1 naïve patient (cost saving is 9,4-10,4%). DCV/ASV and PTV/OBV/DSV/r SVR12 costs are comparable and significantly lower than PegIFN-based regimen: PegIFN/RBV/SMV and PegIFN/RBV/BCV. 4 weeks stop rules due to therapy inefficiency for PegIFN/RBV/SMV regimen could cut cost by 12,6% и 28,0% among patients without and cirrhosis accordingly. By way PTV/OBV/DSV/r is the most cost effective versus PegIFN/RBV/SMV. PTV/OBV/DSV/r as the first line therapy for PegIFN experienced patients provides budget saving 118,2 thousand RUB or 12,2% of budget.Conclusion: Right now PTV/OBV/DSV/r regimen is the most cost effective the first line therapy for naïve patients.